KONTEKSTUALISASI HADIS DALAM KEHIDUPAN BERBANGSA DAN BERBUDAYA - Suryadilaga, Muhammad Alfatih (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2017)
The Hadith for Muslims is a source of Islamic teachings. Therefore, in the life of a Muslim both individually and in groups and in the life of the nation and cultured is stained from the values of Islamic teachings. In the present context along with the development of science and technology and is encouraged to inherit the Prophet's legacy. This makes the importance of contextualization in the understanding of hadith. One form offered is through a hermeneutic approach. This includes the hadith in the life of the nation and the state because of the difference in social context, culture and political system. This effort is to keep the hadith from extinction and can be carried out in context. As a messenger of Allah swt., The Prophet Muhammad. Build a civilized and state society in line with the basic principles of Islam. What was built and developed by the Prophet Sometimes opposed to the tradition that developed before Islam came.